Faculty of Business and Economics, University of Pécs graduates on the labor market - Sipos Norbert; Principles of Scientific Management : International Scientific Conference Szeged 2011 (University of Szeged Faculty of Economics and Business Administration Szeged, 2013)
The topic of the study is the human resource management regarding the different areas of job finding questions of the newly entrants to the market, precisely the graduates, particularly those of the University of Pécs, Faculty of Business and Economics (UP FBE). The Graduate Follow-Up System can be mentioned among the labor-market fit related researches, which is an obligatory task for the higher education institutes. In the analysis I use the research data of the last two years conducted at the University of Pécs. I identify peculiarities, to which we can obtain such cluster groups that allow the creation of an effective support system. The focused energy and resource investment is more effective if it is based on specific training and education packages offered within the Alumni framework. It can increase the results of an even more successful Alma Mater service; furthermore it can improve the self-identification of the institution. From the several motivation-theories, I evaluate the results of the labor-related scores with the findings of Herzberg’s two-factor model. I hypothesized that in general the motivator and hygiene factors can be shown as well, and within the motivator-guided graduates, we can observe an advantage comparing to the hygiene-guided ones. The sample is representative which allows to deduce some findings about the main characteristics of the graduates of the Faculty of Business and Economics. Due to the Bologna Process a new higher education system is raising and formulating which pushes the students to face new challenges, and to create different types of expectations about the goals of their studies. The study on the one hand is a guide for future students who can have a first-hand experience from the graduates working on the labor market, on the other hand the researches can observe the sample of ‘Pécsiközgáz’ graduates.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok